Modification Of Measurement Tools On Cmm Machine To Increase The Accuracy Of The Sport Type K64 Production Process - Komarudin Komarudin; Aditya Rian Wibowo (Dinasti International Journal of Education Management And Social Science, 2024)
New technological innovations in the design and production of motorized vehicles continue to be carried out to maintain product quality and have high-priority safety factors. The tool used by the CMM (Coordinate Measuring Machine) to measure product dimensions must have a very precise level of accuracy. The disadvantage is that it must be measured while still, so it requires tools. The limitation of the problem only focuses on modifying the measuring tools on the CMM machine for the Swing Arm Motor Sport Type K64 product. The aim of this research is to develop measuring tools to achieve tighter dimensional tolerances, increase the accuracy of the production process, and make recommendations for tools to increase measurement accuracy. The method used is a quantitative method. The results obtained show that the simulation and implementation of the K64 swingarm measuring jig show positive and satisfactory results. By modifying the measuring tools on the Coordinate Measuring Machine (CMM), it has succeeded in increasing the accuracy of measuring the K64-type sports motorbike swingarm components. These modifications have a significant impact on improving the accuracy of the swingarm production process in endpiece distance (average deviation percentage 0.05%) and collar distance (average deviation percentage 0.05%), and apart from increasing accuracy, this modification also helps in speeding up the production process and changing the cycle. Time, which was originally 12 minutes, became 8 minutes per unit.